The optimal location of tanks in water distribution networks using failure tolerance - Kapata, Aaron Kalonji; Ilemobade, Adesola (Frontiers in Water, 2025)
The location of tanks impacts the optimal design and reliability of water distribution networks. However, contention exists in the literature regarding the best location for tanks. The aim of this study was therefore to develop a tool to compute failure tolerance when pipe failure occurs in a water distribution network, and as a consequence, to determine the optimal location of a tank(s). To achieve this, five optimal designs of the Anytown Network (ATN), which is a benchmark water distribution network in the literature, were selected. These designs, which recommended additional tanks at different locations of the network, were hydraulically simulated using pressure driven analysis in EPANET 2.2, and these results validated. To compute failure tolerance, a Microsoft Excel® tool was developed, validated and applied to the hydraulically simulated results of the optimal ATN designs. The comparison of the failure tolerance values generated revealed the influence of tank location on the ATN reliability during pipe failure i.e., while each optimal ATN design generated a failure tolerance > 0.68 (a less vulnerable network), the best location for an additional tank(s) was downstream of the demand center. Incidentally, this design emerged as the cheapest and therefore points to the fact that a higher network reliability need not be a more expensive network.